2006
DOI: 10.3171/spi.2006.4.4.273
|View full text |Cite
|
Sign up to set email alerts
|

Effect of approach side during anterior cervical discectomy and fusion on the incidence of recurrent laryngeal nerve injury

Abstract: Object This retrospective study was designed to determine whether side of approach during instrumented, one- or two-level primary anterior cervical discectomy and fusion (ACDF) affects the incidence of recurrent laryngeal nerve (RLN) injury diagnosed by observation of the vocal cords (OVC). Methods Records of all patients who underwent one- or two-level instrumented primary ACDF (418 patients) between Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
1
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(45 citation statements)
references
References 22 publications
0
36
1
8
Order By: Relevance
“…The incidence of the recurrent laryngeal nerve branch ranged from Ͻ1% to 6% for thyroidectomy, from Ͻ1% to 8% for carotid endarterectomy, and from 1.3% to 2.6% for anterior cervical spine surgery. 4,[9][10][11][12] The recurrent laryngeal fibers are medially placed in the vagal trunk. 3,13 For anterior variation, the VN was superficial and medial to the CCA, and nerve injury may occur during dissection by a diathermy burn or mechanical stretching during carotid endarterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of the recurrent laryngeal nerve branch ranged from Ͻ1% to 6% for thyroidectomy, from Ͻ1% to 8% for carotid endarterectomy, and from 1.3% to 2.6% for anterior cervical spine surgery. 4,[9][10][11][12] The recurrent laryngeal fibers are medially placed in the vagal trunk. 3,13 For anterior variation, the VN was superficial and medial to the CCA, and nerve injury may occur during dissection by a diathermy burn or mechanical stretching during carotid endarterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…RLN palsy accounts for most of these cases, and although SLN injury may occur, findings can be subtle. The reported incidence of RLN injury in a combined series of more than 3,000 cases in which a head and neck surgeon was not involved in the exposure was between 1.9% and 5% 7, 11–13. One study has shown a similar rate of temporary RLN palsy, but recovery occurred in many of these (Table I).…”
Section: Introductionmentioning
confidence: 99%
“…Structures trapped between the retractor and the endotracheal tube cuff, like the recurrent laryngeal nerve, may be compromised. In patients who were treated with anterior cervical discectomy and fusion, the incidence of recurrent laryngeal nerve injury is about 2%, irrespective of the side of approach [3]. Consequently, dysphagia, hoarseness, and sore throat may occur.…”
Section: Introductionmentioning
confidence: 99%